Tinjauan Etika Kristen Terhadap Beban Ganda Generasi Sandwich - Telaumbanua, Agus Arda Setiawan; Sumual, Elisa Nimbo; Arifianto, Yonatan Alex (Teokristi: Jurnal Teologi Kontekstual dan Pelayanan Kristiani, 2025)
Abstract: The sandwich generation phenomenon refers to adults who are caught between the obligations of caring for their aging parents and raising their own children. This situation creates complex pressures, including financial, emotional, and social aspects. This article aims to examine the double burden faced by the sandwich generation from a Christian ethical perspective using a qualitative method based on a literature review. The Bible emphasizes the importance of honoring parents and the responsibility to raise children with love as fundamental principles in family life. Christian ethics provide a normative framework so that responsibilities toward parents and children are not viewed merely as a social burden, but as an expression of obedience to God. The principles of love, justice, stewardship, and Christian spirituality serve as a practical foundation for balancing roles in the nuclear family without neglecting intergenerational obligations. Thus, the application of Christian ethics is expected to help the sandwich generation live a more balanced, meaningful life in accordance with God's will. Keywords: Ethics, Double Burden, Sandwich Generation